Peran Orang Tua terhadap Hasil Belajar Matematika Materi Aljabar di Masa Pandemi COVID-19 - Setya Selaksa Mentari; Yatha Yuni; Niken Vioreza (Pendidikan Matematika STKIP Kusuma Negara, 2021)
The role of parents is needed in the education of children. The role of parents in education makes the quality of children's education better. The purpose of the study was to determine the relationship between the role of parents and the mathematics learning outcomes of Algebra during the Corona Virus Disease 2019 (COVID-19) Pandemic. The research sample was 72 junior high school students in class VII. This study uses quantitative methods with survey techniques. The instrument is a questionnaire and an objective test. The prerequisite test used the Liliefors test, and the data were normally distributed. An analysis of the regression equation shows there is a positive relationship between the two variables. Hypothesis testing using the product-moment correlation test is obtained rcount more than rtable at a significant level of 5%. Because rcount more than rtable, it can be concluded that there is a strong relationship between the role of parents and learning outcomes in mathematics. Based on the correlation t-test, obtained tcount>ttable with db=70. The conclusion is that there is a significant positive relationship between the role of parents and the mathematics learning outcomes of junior high school students. Parents' attention contributes 57.15% to mathematics learning outcomes.